2022
DOI: 10.1101/2022.02.27.481627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinically oriented prediction of patient response to targeted and immunotherapies from the tumor transcriptome

Abstract: Precision oncology is gradually advancing into mainstream clinical practice, demonstrating significant survival benefits. However, eligibility and response rates remain limited in many cases, calling for better predictive biomarkers. Here we present ENLIGHT, a transcriptomics-based computational approach that identifies clinically relevant genomic interactions and uses them to predict patients' response to a variety of therapies in multiple cancer types without training on previous response data. We study ENLI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 80 publications
(163 reference statements)
0
19
0
Order By: Relevance
“…First, we applied DeepPT to predict the patient transcriptomics from their H&E slides. Second, based on this predicted gene expression, we used the precision oncology algorithm, ENLIGHT [33], to predict the patients' response from the predicted expression.…”
Section: Predicting Treatment Response From Deeppt-predicted Gene Exp...mentioning
confidence: 99%
See 2 more Smart Citations
“…First, we applied DeepPT to predict the patient transcriptomics from their H&E slides. Second, based on this predicted gene expression, we used the precision oncology algorithm, ENLIGHT [33], to predict the patients' response from the predicted expression.…”
Section: Predicting Treatment Response From Deeppt-predicted Gene Exp...mentioning
confidence: 99%
“…Data utilized in this analysis included the response to therapy by residual cancer burden criteria and the fresh frozen H&E-stained primary tumor slides. were greater/equal (lesser) than a decision threshold value of 0.54, a threshold that was fixed and determined already in [33], again, on completely independent data. The same threshold was used here, without any training or modification, both for ENLIGHT-DeepPT and ENLIGHTactual.…”
Section: Predicting Treatment Response From Deeppt-predicted Gene Exp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have recently attempted to incorporate multiple sources of information into cutting-edge machine learning approaches in order to create clinically oriented predictions of patient responses to medications. I-PREDICT (7), NCI-MATCH (8), MI-ONCOSEQ (9), WINTHER (10), ONCO-TARGET/ONCOTREAT (11), SELECT (12), and ENLIGHT (13) are studies that aim to match patients with therapies and predict their impact on treatment outcome using DNA biomarkers, genomic and transcriptomic information, protein-protein interaction networks, synthetic lethal and/or synthetic rescue interactions among other factors (713). However, developing such studies requires data from a large number of patients as well as extensive knowledge of the exact molecular targets for each of the drugs under investigation, limiting their applicability (14).…”
Section: Introductionmentioning
confidence: 99%
“…However, a large fraction of cancer patients still do not bene t from such targeted therapies, and efforts are hence much needed to nd ways to analyze other molecular omics data types to bene t more patients. Addressing this challenge, recent studies have begun to explore the bene t of collecting and analyzing bulk tumor transcriptomics data to guide cancer patient treatment (Beaubier et al, 2019;Hayashi et al, 2020;Rodon et al, 2019;Tanioka et al, 2018;Vaske et al, 2019;Wong et al, 2020, Lee et al, 2021, Dinstag et al, 2022. These studies have demonstrated the potential of such approaches to complement DNA sequencing approaches in increasing the bene t of omics-guided precision treatments to patients.…”
Section: Introductionmentioning
confidence: 99%